Efektivitas Trauma Healing Dalam Mengurangi Trauma Psikologis Pada Korban Kecelakaan Bus Pariwisata di Pagar Alam Tahun 2023 - Hanifah, Abu; Rahma, Zanjabila (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2024)
The World Health Organization (WHO) states that there are as many as 1.25 million victims of traffic accidents every year, and 20-50 million people face injuries due to traffic accidents. Accidents have an impact that can be felt on the human body, such as physical injuries that result in trauma to the individual. This accident is a symptom of trauma which affects the brain's memory that it interferes with a person carrying out daily activities, such as always being alert. In this study, the sample taken experienced trauma due to a tourist bus accident because the accident resulted in physical disability and disrupted daily activities. The sample felt anxious and remembered the bus accident every night. This research aims to reduce the subject's psychological trauma due to the tourist bus accident by applying Al-Quran Murotal Therapy. The method in this research is a One Shot Case Study Design Experimental research (One Case Design) meaning it consists of one group that is given treatment (Murotal Al-Quran Therapy) then observes the symptoms that occur, then conclusions are drawn. The application of Al-Quran murotal therapy in this research was carried out routinely 2 times a day for 26 weeks. From the subject's 26-week journey in applying Murotal Al-Quran therapy, researchers saw that the journey in physical and mental healing were in line with rational thinking.Keywords - Accidents, Psychological Trauma, Murotal Al-Quran.